Tissue regeneration : where nano-structure meets biology - Liu, Qing, 1962 June 22-; Wang, Hongjun, 1970- (Frontiers in nanobiomedical research ;, 2014)
This unique volume presents the recent advances in tissue regeneration. The authors are all active researchers in their respective fields with extensive experiences. The focus of the book is on the use of stem cells and nano-structured biomaterials for tissue regeneration/tissue engineering. It includes the use of stem cells, naturally derived extracellular matrix (ECM), synthetic biomimetic nano-fibers, synthetic nano-structured ceramics and synthetic nano-structured polymer/ceramic composites that can help/promote tissue regeneration. Methods on how to produce these nano-structured biomaterials are also discussed in several chapters. Future challenges and perspectives in the field of regenerative medicine (tissue regeneration) are also discussed.